Determinants of the valuation allowance for deferred tax assets under SFAS No. 109. - Miller, Gregory S.; Skinner, Douglas J. (The Accounting Review, 1998)
This paper explores the determinants of the valuation allowance for deferred tax assets under SFAS No.109. We find that, consistent with SFAS No. 109, the allowance is larger for firms with relatively more deferred tax assets and smaller for firms with higher levels of expected future taxable income. The most important explanatory variable for the valuation allowance is the level of firms' tax credit and tax loss carryforwards, consistent with these items being more difficult to realize. We find little evidence that managers use the valuation allowance for earnings management purposes, although these tests may not be very powerful.